Drosophila HP1c isoform interacts with the zinc-finger proteins WOC and Relative-of-WOC to regulate gene expression. - Font-Burgada, J.; Rossell, D.; Auer, H.; Azorín, F. (Genes & Development, 2008)
Heterochromatin protein 1 (HP1) proteins are conserved in eukaryotes, with most species containing several isoforms. Based on the properties of Drosophila HP1a, it was proposed that HP1s bind H3K9me2,3 and recruit factors involved in heterochromatin assembly and silencing. Yet, it is unclear whether this general picture applies to all HP1 isoforms and functional contexts. Here, we report that Drosophila HP1c regulates gene expression, as (1) it localizes to active chromatin domains, where it extensively colocalizes with the poised form of RNApolymerase II (RNApol II), Pol IIo(ser5), and H3K4me3, suggesting a contribution to transcriptional regulation; (2) its targeting to a reporter gene does not induce silencing but, on the contrary, increases its expression, and (3) it interacts with the zinc-finger proteins WOC (without children) and Relative-of-WOC (ROW), which are putative transcription factors. Here, we also show that, although HP1c efficiently binds H3K9me2,3 in vitro, its binding to chromatin strictly depends on both WOC and ROW. Moreover, expression profiling indicates that HP1c, WOC, and ROW regulate a common gene expression program that, in part, is executed in the context of the nervous system. From this study, which unveils the essential contribution of DNA-binding proteins to HP1c functionality and recruitment, HP1 proteins emerge as an increasingly diverse family of chromatin regulators.